HIV in China : understanding the social aspects of the epidemic - Jing, Jun, 1957-; Worth, Heather (UNSW Press, 2010)
"The result of collaboration between the University of New South Wales and the Tsinghua University in Beijing, this unique chronicle maps some of the most important social, political, and cultural characteristics of the HIV epidemic in China. Demonstrating that the epidemic was propelled by three main economic drivers--the blood trade, the drug trade, and the sex trade--this informative compilation of essays uncovers the hidden truths about the spread of HIV and analyzes its social impacts"--Provided by publisher.